(untitled) - Prince, Dennis L. (New York, NY., 2005)
More than 95 million people now use eBay. This essential organizer is a workbook that walks the reader through the entire selling process--from logging on and listing items to selling, shipping, and keeping records. It even includes fill-in-theblank forms and checklists that help the reader organize sales faster and easier. Both novice and experienced sellers will learn how to: Create irresistible listings for a surefire sale, Determine what's hot and what's not, Manage multiple listings and keep track of records and Set up an auction office and website.
Keywords: eBay ( Firm ),Internet auctions